2022
DOI: 10.1111/1759-7714.14527
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of ABCB1 and ABCG2 overcame resistance to topoisomerase inhibitors in small cell lung cancer

Abstract: Background Small cell lung cancer (SCLC) is a highly aggressive disease with a poor prognosis. Although most patients initially respond to topoisomerase inhibitors, resistance rapidly emerges. The aim, therefore, is to overcome resistance to topoisomerase I (irinotecan) or II (etoposide) inhibitors in SCLCs. Methods To identify key factors in the chemoresistance of SCLCs, we established four cell lines resistant to etoposide or an active metabolite of irinotecan, SN‐38, from SCLC cell lines and evaluated RNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Shivhare and Das [43] reported the reduction of the inhibitory concentration of doxorubicin and tamoxifen in an in vitro breast cancer study by combining the chemotherapeutics with a pan-ABC transporter inhibitor. Furthermore, in a study on small cell lung cancer, treatment with the ABC transporter inhibitors elacridar and tariquidar restored the cells' sensitivity to topoisomerase inhibitors [45].…”
Section: Discussionmentioning
confidence: 99%
“…Shivhare and Das [43] reported the reduction of the inhibitory concentration of doxorubicin and tamoxifen in an in vitro breast cancer study by combining the chemotherapeutics with a pan-ABC transporter inhibitor. Furthermore, in a study on small cell lung cancer, treatment with the ABC transporter inhibitors elacridar and tariquidar restored the cells' sensitivity to topoisomerase inhibitors [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in chronic myeloid leukemia, combining elacridar with imatinib attenuated the drug efflux transporter-associated resistance [ 53 ]. Moreover, elacridar overcame resistance to topoisomerase inhibitors in small-cell lung [ 54 ] and gastric [ 55 ] cancers. Additionally, in prostate cancer, it was demonstrated that the resistance to olaparib might also be overcome using elacridar [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABCG2, an ATPbinding cassette efflux transporter, has been implicated in conferring resistance to clinically used anticancer drugs, including topotecan and irinotecan [130,131]. Inhibitory interventions, such as elacridar and tariquidar, small-molecule inhibitors, exhibit promise by inducing synergistic apoptosis and heightened drug sensitivity in small cell lung cancer (SCLC) cells resistant to VP-16 or SN-38 [132].…”
Section: Abc Transporter-mediated Resistance Of Topo Drugsmentioning
confidence: 99%